Umbilical Hernia Repair and Pregnancy: Before, during, after… - Kulacoglu, Hakan (Frontiers in Surgery, 2018)
Umbilical hernias are more common in women than men. Pregnancy may cause herniation or render a preexisting one apparent because of progressively raised intraabdominal pressure. The incidence of umbilical hernia among pregnancies is 0.08%. Surgical algorithm for a pregnant woman with a hernia is not thoroughly clear. There is no consensus about the timing of surgery for an umbilical hernia in a woman either who is already pregnant or planning a pregnancy. If the hernia is incarcerated or strangulated at the time of diagnosis an emergency repair is inevitable. If the hernia is not complicated but symptomatic an elective repair should be proposed. When the patient has a small and asymptomatic hernia it may be better to postpone the repair until she gives birth. If the hernia is repaired by suture alone, a high risk of recurrence exists during pregnancy. Umbilical hernia repair during pregnancy can be performed with minimal morbidity to the mother and baby. Second trimester is a proper timing for surgery. Asymptomatic hernias can be repaired following childbirth or at the time of cesarean section. Elective repair after childbirth is possible as early as postpartum 8th week. A one-year interval can give the patient a very smooth convalescence including hormonal stabilization and return to normal body weight. Moreover, surgery can be postponed for a longer time even after another pregnancy if the patients would like to have more children. Diastasis recti is very frequent in pregnancy. It may persist in postpartum period. A high recurrence risk is expected in patients with rectus diastasis. This risk is especially high after suture repairs. Mesh repairs should be considered in this situation.